Multi-omic analysis of precocious puberty girls: pathway changes and metabolite validation - Zhou, Fang; Mao, Jianhong; Jin, Zhenzhen; Zhu, Li; Li, Xiaofang (Frontiers in Endocrinology, 2024)
Objective: Precocious puberty (PP) is a prevalent endocrine disorder affecting on the physical and mental well-being of children. Identifying the triggering factors of PP has become a central issue. This study seeks to investigate the metabolomic and transcriptomic alterations in PP.Material and methods: First, 37 school-aged girls diagnosed with PP and 25 age-matched prepubertal control girls were recruited, and the fecal samples were collected for non-targeted metabolomics analysis to screen for differentially expressed metabolites (DEMs). Subsequently, an animal model of PP was constructed by danazol administration to neonatal female rats, and both fecal non-targeted metabolomics and serum next-generation transcriptomic sequencing were performed to screen DEMs and differentially expressed genes (DEGs) in PP. Moreover, the DEM co-existing in clinical and animal model was administrated to PP rats to explore the role of the target metabolite in PP.Results: A total of 24 DEMs in PP clinical samples, 180 DEMs and 425 DEGs in PP animal samples were identified, respectively. KEGG pathway analysis manifest that these DEMs and DEGs were enriched in disease-associated pathways, including fatty acids synthesis, glycerolipid metabolism, pyrimidine metabolism, steroid hormone biosynthesis, progesterone-mediated oocyte maturation, GnRH signaling pathway, forming a tight DEMs-DEGs-pathways regulatory network.Further DEM validation demonstrated that thymine supplementation delayed the opening of the vagina and development of PP in model rats.This study reveals that the metabolomic and transcriptomic changes, along with enriched pathways, are implicated with PP based on clinical and animal analyses. The findings may provide new strategies and research avenues for PP treatment.